Characterization of herb residue and high ash-containing paper sludge blends from fixed bed pyrolysis. (June 2018) - Li, Tiantao; Guo, Feiqiang; Li, Xiaolei; Liu, Yuan; Peng, Kuangye; Jiang, Xiaochen; Guo, Chenglong
Highlights: Catalytic effect of paper sludge during herb residue pyrolysis was investigated. Catalytic effect of paper sludge enhanced gas yield and inhibited tar yield. H2 and CO2 were promoted while CH4 was inhibited by paper sludge below 900 °C. Ash particles from paper sludge adhered to herb residue char after pyrolysis. Paper sludge favored the forming of heavier polycyclic aromatic hydrocarbons. Abstract: High ash-containing paper sludge which is rich in various metal oxides is employed in herb residue pyrolysis to enhance the yield of fuel gas and reduce tar yield in a drop tube fixed bed reactor. Effects of heat treatment temperature and blending ratio of paper sludge on the yields and composition of pyrolysis products (gas, tar and char) were investigated. Results indicate that paper sludge shows a significantly catalytic effect during the pyrolysis processes of herb residue, accelerating the pyrolysis reactions. The catalytic effect resulted in an increase in gas yield but a decrease in tar yield. The catalytic effect degree is affected by the paper sludge proportions, and the strongest catalytic effect of paper sludge is noted at its blending ratio of 50%. At temperature lower than 900 °C, the catalytic effect of paper sludge in the pyrolysis of herb residue promotes the formation of H2 and CO2, inhibits the formation of CH4, but shows slight influence on the formations of CO, while the formation of the four gas components was all promoted at 900 °C. SEM results of residue char show that ash particles from paper sludge adhere to the surface of the herb residue char after pyrolysis, which may promote the pyrolysis process of herb residue for more gas releasing. FT-IR results indicate that most functional groups disappear after pyrolysis. The addition of paper sludge promotes deoxidisation and aromatization reactions of hetero atoms tars, forming heavier polycyclic aromatic hydrocarbons and leading to tar yield decrease.